Wire plus arc additive manufactured functional steel surfaces enhanced by rolling - Dirisu, Philip; Ganguly, Supriyo (Elsevier, 2019)
Surface waviness (SW) is one of the major problems confronting the economical use of as-deposited components made with the wire plus arc additive manufactured (WAAM) process. The SW acts as a stress raiser, thereby reducing the tensile properties and fatigue life of the component. In this study, the effect of compressive residual stress on the mechanical and fatigue behaviour of the as-deposited WAAM mild steel component was carried out using a process which combines deposition and rolling on the WAAM component surface. The fractured faces and microstructure were characterised by a scanning electron and optical microscope. The microstructural changes were characterised by X-ray diffraction techniques. The results revealed that an increase in the notch radius and compressive stress induced by rolling on the as-deposited condition reduced the SW from 0.18 to 0.08 mm with a reduction of stress concentration, consequently reducing crack initiation and propagation and improving fatigue life. This work shows that rolling has a dual effect on as-deposited WAAM mild steel components with a new functional surface.
Keywords: Functional surfaces; Fatigue life; Tensile strength; WAAM; Rolling